(untitled) (Salud, Arte y Cuidado, 2026)
The objective of this research was to know the characteristics of the state of mental health in university students of the nursing degree, at the Universidad Centroccidental Lisandro Alvarado (UCLA). For data collection, the Goldberg General Health Inventory was used, and the results were analyzed with the GraphPad Prism 8 statistical program. This inventory was applied to a sample of 43 nursing students from the Universidad Centroccidental Lisandro Alvarado, Lara, Barquisimeto, of which 81% were female, and 19% were male, who are studying in the first semester of the degree in nursing. 89% of the students range between 17 and 19 years old. Once the subscales of Goldberg’s general health questionnaire have been analyzed, it is observed that the percentage of cases detected with mental health problems, which includes probable cases of psychosomatic symptoms, is 28.6%, anxiety and insomnia, 59.5%, social dysfunction, 11.9%, and depression, 7.1%. The mental health of college students is a topic of growing concern due to the increase in difficulties related to psychological well-being in this population